2020
DOI: 10.1302/0301-620x.102b10.bjj-2019-1112.r1
|View full text |Cite
|
Sign up to set email alerts
|

The surgical repair of proximal hamstring avulsions

Abstract: Aims Despite the increase in the surgical repair of proximal hamstring tears, there exists a lack of consensus in the optimal timing for surgery. There is also disagreement on how partial tears managed surgically compare with complete tears repaired surgically. This study aims to compare the mid-term functional outcomes in, and operating time required for, complete and partial proximal hamstring avulsions, that are repaired both acutely and chronically. Methods This is a prospective series of 156 proximal hams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…The structure and function of articular cartilage are complex, and small trauma may cause its damage. 10 This experiment shows that 3D SPGR sequence imaging can more accurately evaluate knee cartilage lesions with a sensitivity of 64%, the specificity of 87%, and accuracy of 80%. 11 In this study, 3D FIESTA images showed a high agreement rate (60%) between the diagnosis of knee hyaline cartilage lesions and surgical results; the sensitivity and specificity were 54% and 87%.…”
Section: Discussionmentioning
confidence: 76%
“…The structure and function of articular cartilage are complex, and small trauma may cause its damage. 10 This experiment shows that 3D SPGR sequence imaging can more accurately evaluate knee cartilage lesions with a sensitivity of 64%, the specificity of 87%, and accuracy of 80%. 11 In this study, 3D FIESTA images showed a high agreement rate (60%) between the diagnosis of knee hyaline cartilage lesions and surgical results; the sensitivity and specificity were 54% and 87%.…”
Section: Discussionmentioning
confidence: 76%
“…Acute avulsions were arbitrarily defined as patients who were operatively treated within 6 weeks after the injury, while chronic avulsions underwent surgery after 6 weeks and analysis was done from studies where comparison was possible [ 7 , 13 , 14 , 17–21 , 23 , 24 , 31 , 35 ] (815 patients, 502 acute and 313 chronic). The mean time from injury to intervention for the acute and chronic groups was 2.8 and 46 weeks, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Acute surgical repair is the recommended treatment for active patients with acute and retracted complete 2-tendon or 3-tendon proximal hamstring avulsion injuries and leads to positive functional outcomes 3,6,22 . The bilateral nature of this patient's injury presented us with a clinical challenge of deciding between a sequential or simultaneous repair.…”
Section: Discussionmentioning
confidence: 99%